Why Siblings? Introducing the "Sibling Trauma" and the "Law of the Mother" on the "Horizontal" Axis. Issue 1 (31st December 2022) - Mitchell, Juliet
ABSTRACT: Siblings came to me as a contradictory experience: a Eureka-like ecstatic revelation subdued by a numb sense of tired relief. I had struggled for years with what was intended as a book on male hysteria. Although in Studies in Hysteria (1895) Freud published only cases of female hysteria, it was his insistence on the existence of hysteria in men that was the underlying foundation–stone of psychoanalysis. Without it, hysteria could not have been a universal; no universal, no unconscious, no psychoanalysis. But likewise it was in discarding his trauma theory of the genesis of hysteria in favor of the concept of desire that made Freud overjoyed to give up his "neurotica" and confirm the inauguration of a new knowledge – psychoanalysis.